2008
DOI: 10.1111/j.1365-2672.2008.03930.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flagella expression on adhesion ofAchromobacter piechaudiito chalk surfaces

Abstract: Aims:  To examine flagella role and cell motility in adhesion of Achromobacter piechaudii to chalk. Methods and Results:  Transmission electron microscopy revealed that stationary cells have thicker and longer flagella than logarithmic cells. SDS‐PAGE analysis showed that flagellin was more abundant in stationary cells than logarithmic ones. Sonication or inhibition of flagellin synthesis caused a 30% reduction in adhesion to chalk. Preincubation of chalk with flagella extracts reduced adhesion, by 50%. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…This observation demonstrates that, although Rhizobium sp. NT-26 has a preferential motile life style in the presence of arsenite, flagella have a role as adhesive appendages in the first steps of biofilm formation, which has been shown previously in other studies (Kirov et al 2004; Nejidat et al 2008). This result is in agreement with those obtained with H. arsenicoxydans , where mutations resulting in nonfunctional flagella led to a more rapid adhesion as compared with the wild-type.…”
Section: Resultssupporting
confidence: 80%
“…This observation demonstrates that, although Rhizobium sp. NT-26 has a preferential motile life style in the presence of arsenite, flagella have a role as adhesive appendages in the first steps of biofilm formation, which has been shown previously in other studies (Kirov et al 2004; Nejidat et al 2008). This result is in agreement with those obtained with H. arsenicoxydans , where mutations resulting in nonfunctional flagella led to a more rapid adhesion as compared with the wild-type.…”
Section: Resultssupporting
confidence: 80%
“…The fliL gene is the first gene of the fliLMNOPQR operon, belonging to the class 2 genes, and encoding flagellar structural proteins implicated in the specification of the basal body and hook structure (Macnab, 2004). We showed that the mutant displays wild-type surface properties, including the presence of a flagellum, which is known to influence the surface properties of the cell and can act as an adhesive appendage (Kirov et al, 2004;Nejidat et al, 2008). In the absence of arsenite, the mutant also exhibited wildtype biofilm formation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Flagella were also described as contributing to the adhesion to inert surfaces of other micro‐organisms such as Campylobacter jejuni (Joshua et al. 2006), Achromobacter piechaudii (Nejidat et al. 2008) and Aeromonas caviae (Kirov et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of flagella to the biofilm initiation of L. monocytogenes is more consensual (Vatanyopaisarn et al 2000;Lemon et al 2007;Todhanakasem and Young 2008). Flagella were also described as contributing to the adhesion to inert surfaces of other microorganisms such as Campylobacter jejuni (Joshua et al 2006), Achromobacter piechaudii (Nejidat et al 2008) and Aeromonas caviae (Kirov et al 2004). Generally, it is assumed that flagellum expression in L. monocytogenes is repressed at temperatures above 25°C (Peel et al 1988).…”
Section: Discussionmentioning
confidence: 99%